Prática docente em Educação Ambiental: pesquisa-ação colaborativa em uma escola pública estadual - MATTOS, Ariane Barilli de (2019)
The present master's research was developed within the scope of the Post-Graduation Program in Education of the Universidade do Oeste Paulista (UNOESTE) and is linked to the line of research entitled "Training and Pedagogical Practice of the Professional Teacher". It was funded by the Coordination for the Improvement of Higher Education Personnel (CAPES). The purpose of this study was to analyze and understand the contributions of a collaborative action research to the school and to the teaching practice of Elementary and Secondary School teachers of a state public institution when working with Environmental Education. The research was carried out with five teachers from different disciplines of Primary and Secondary Education of a state public school located in a medium sized city in the interior of the state of São Paulo. This research fits the qualitative approach and the methodological option adopted for its accomplishment was collaborative action research. The theoretical option assumed was that of Environmental Education from a critical-reflective perspective. As a methodological procedure, a bibliographical search was carried out with searches in the digital databases, such as CAPES, SciELO and BDTD to give subsidy to the theoretical support of the study, and for the collection of data and information, a questionnaire was applied and periodic meetings were held with the teachers participating in the research, as well as participant observation. For the analysis of data and information, triangulation was used. The results of the research revealed that the study made possible the participation of the teachers and, in particular, the protagonism of the students in the accomplishment of the actions in the school, allowing the critical reflection of these on their living space, that is, the school space, providing the development of environmental awareness in relation to the closest environment, inciting, especially in students, the idea of belonging / place. The actions taken, despite some limitations, allowed the teachers to critically reflect on their practice related to Environmental Education, which provided, therefore, contributions, as well as improvements and / or alternative / innovative forms for the action of these related professionals thematic.